Upaya Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran IPA tentang Materi Gaya Melalui Metode Inquiri - Dian Amalia (SAP (Susunan Artikel Pendidikan), 2022)
The purpose of this study is to determine the increase in student learning outcomes regarding the subject matter of science subject style in class VIII.A of SMP Negeri 276 Jakarta in the odd semester of the 2019/2020 academic year through the use of the Inquiry Method. This research was conducted at SMP Negeri 276 Jakarta in the 2019/2020 school year with the research subjects was VIII.A students consisting of 20 male students and 16 female students. The method used was a class action research method consisting of two cycles. In the first cycle, learning was carried out using the Inquiry Method, while in the second cycle, the Inquiry Method has been refined. Each cycle consisted of four stages of research, namely planning, implementing actions, observing, and reflecting. The results of this study indicated that the use of the Inquiry Method can improve student learning outcomes about Style material in science subjects in class VIII A SMP Negeri 276 Jakarta in the odd semester of the 2019/2020 academic year seen there is an increase in the value of learning outcomes.